Cerebral Embolization of Ethiodized Oil following Intranodal Lymphangiography - Sheybani, Arman; Gaba, Ron C.; Minocha, Jeet (Seminars in Interventional Radiology, 2015)
Intranodal lymphangiography (IL) has supplanted pedal lymphangiography (PL) as an easier and more practical approach to opacifying lymphatic vessels for interventional radiologists treating refractory chyle leaks. As more interventional radiologists—many of who are not trained in or have not performed PL—incorporate IL into their practice, it is imperative that they be familiar with the risks of lymphangiography, including pulmonary and systemic embolization of oily contrast material. Herein, the authors report a devastating case of cerebral embolization of ethiodized oil following IL and review the literature regarding systemic embolization following lymphangiography.
Keywords: interventional radiology; stroke; complication; lymphangiogram